Case Study Of IT Shared Services In Telekom Malaysia - Othman, Maz Hiza Bazly (2007)
This study discusses about shared services as a strategy in organizationl change in large organizations namely, Telekom. To enhance and contribute to awareness, this study explore the opinions and researches of others shared services and compare with the current scenario which is reorganization of shared services as an option in big organization, particularly in the service-based and IT-enabled industry such as telecommunication.